A quantitative methodological framework to classify corporate sustainability behavior - Ioannis E. Nikolaou; Nikolaos S. Trevlopoulos; Konstantinos I. Evangelinos; Anastasios Sepetis; Thomas A. Tsalis (Clean Technologies and Environmental Policy, 2026)

Circular Economy Behavior and Sustainable Healthcare - Anastasios Sepetis; Ioannis Parlavantzas (Circular Economy and Sustainability, 2025)
The healthcare sector faces significant challenges related to resource constraints, environmental impacts and increasing demand for services. This study examines how the integration of circular economy principles and organizational behavior can enhance the sustainability of healthcare systems. By implementing circular economy practices - such as waste reduction, material reuse and recycling - healthcare organizations can optimize resource use and minimize their ecological footprint. In addition, the role of organizational behavior is critical, as effective leadership, employee engagement and a supportive culture can lead to the adoption of sustainable practices that align with the organization’s mission. An integrated approach that combines circular economy strategies with supportive organizational practices enhances system resilience, reduces dependence on finite resources and promotes broader environmental and social sustainability goals. This study scrutinizes the critical role of organizational behavior in terms of management’s perception of climate change, the way a health organization operates in relation to staff mobilization and the views of its own staff always with climate change in mind and its effects. An analysis of a sample of 379 health professionals through a relevant questionnaire from the public and private sectors of the healthcare industry in Greece revealed a significant degree of detachment of the administrations from environmental concerns, with the simultaneous absence of motivation of the staff on corresponding issues, while negative was the health workers’ overall perception of climate, showing significant challenges in communication in addition to education and awareness within the organization. Overall, this research provides a window into the adoption of Organizational Behavior and Circular Economy principles by healthcare organizations in order to ensure their sustainability.